2014
DOI: 10.1093/scan/nsu121
|View full text |Cite
|
Sign up to set email alerts
|

Beautiful friendship: Social sharing of emotions improves subjective feelings and activates the neural reward circuitry

Abstract: Humans have a strong tendency to affiliate with other people, especially in emotional situations. Here, we suggest that a critical mechanism underlying this tendency is that socially sharing emotional experiences is in itself perceived as hedonically positive and thereby contributes to the regulation of individual emotions. We investigated the effect of social sharing of emotions on subjective feelings and neural activity by having pairs of friends view emotional (negative and positive) and neutral pictures ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
73
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 34 publications
13
73
0
Order By: Relevance
“…Previous studies have indicated that our own emotional states are strongly influenced by the presence of others [4–6]. For instance, one’s positive feelings can be elevated when viewing positive stimuli with a friend, compared to viewing alone [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that our own emotional states are strongly influenced by the presence of others [4–6]. For instance, one’s positive feelings can be elevated when viewing positive stimuli with a friend, compared to viewing alone [6].…”
Section: Introductionmentioning
confidence: 99%
“…One of the large‐scale dimensions emerging from the factor analysis assigned high scores to sentences describing people and social interactions. The location of the largest factor‐related cluster (posterior cingulate cortex and the adjacent precuneus region) is known for its role in episodic memory and being a signature of the default mode network [Cavanna and Trimble, ; Gusnard and Raichle, ], and it has also been found to activate during social sharing of emotions versus processing emotion alone [Wagner et al, ], and during thinking about intentional versus physical causality [Ouden et al, ]. Similarly, the medial prefrontal cortex has been associated with social and moral reasoning [Moll et al, ; Van Overwalle, ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the relationships between neural activity and emotional valence have eluded consensus (Lamm et al, 2015; Wagner et al, 2015). In this study, we only measured rs-fMRI and reposting rate of each emotional type in lab, exploring the association between rs-functional connectivity and reposting rate.…”
Section: Discussionmentioning
confidence: 99%